CASTOR: A Calorimeter for Forward Physics at the CMS Experiment, CERN. - Aslanoglou, X.; CMS/CASTOR group, for the (HNPS Advances in Nuclear Physics, 2020)
In the search for Strange Quark Matter (SQM) and Exotic objects in Heavy Ion collisions at high energy, a new Electromagnetic plus Hadronic calorimeter, the CASTOR (Centauros And STrange Objects Research) calorimeter is now under construction. This calorimeter will operate in the experiment CMS at the LHC collider at CERN and is designed for the detection of Strange and Exotic objects at heavy ion collisions. Beam tests of two prototypes in the years 2003, 2004 and 2007 showed a good behavior of the instrument.